Digital natives problems and challenges in learning English - Arti Novia Tiara Kristy; Noor Malihah; Faizal Risdianto; Supardi Supardi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
This research aims to analyze the problems and challenges encountered by Digital Natives and to find out how they overcome them in English learning. The Digital Natives were students of the English Department, IAIN Salatiga, in Academic Year 2017/2018. The methodology of this research was descriptive qualitative. This research used questionnaires and interviews. The questionnaire was used to find out the problem, challenge, and solution of Digital Natives in learning English. The interview section was to collect the information from participants about their experience, the problems and challenges, and how to solve them. This research, it was conducted data analysis by data reduction by simplifying, classifying, and removing unnecessary or irrelevant data to achieve the best finding of the research. The results showed that bad internet signal and connection, the negative effect of the technology and language learning problem. The challenge they frequently have is coping with the problem of lack of English vocabulary and they are being unsociable to the environment. The research showed that technology can be used as an effective digital tool to learn English. It can be seen by the participants’ learning experience. The digital tool assists English learner by overcoming their problems and challenges, what are the participants get more in using the digital tool is how fun the digital tool make easier for English learners... To overcome those problems, they should be wise with their dependence on the gadget and the internet. Then after a long time getting difficult vocabulary, they looked up some online dictionaries and asked to their friends.